THE PERSONALITY OF “BORNO” IN KAU, AKU, DAN SEPUCUK ANGPAU MERAH NOVEL WRITTEN BY TERE LIYE: PSYCHOANALYSIS STUDY - Eka Yuningsih; Nurhayati Nurhayati; Izzah Izzah (University of Kuningan, 2021)
This research aimed to determine the psychological description of the main character, Borno, reviewed from Sigmund Freud’s psychoanalysis. The subject was the novel of Kau, Aku, dan Sepucuk Angpau Merah written by Tere Liye. The applied research methodology was descriptive qualitative. The data of this research consisted of words, phrases, sentences, and discourse related to the main character's personality structures in the novel. The data collection techniques were reading, noting, and analyzing the documents with literature psychological analysis of Sigmund Freud. The novel tells the love story of Borno and Mei due to a pincher, Sepit. At that time, Mei was doing field practice in Pontianak. She crossed the Kapuas river. Borno saw her and fell in love with her, the Chinese-breed girl. The red packet, angpau merah, was left on a pincher made Borno wanted to return it. Borno's struggles to find out her name, Mei, was successful. From the analyzed data, the personality ego frequently appeared in Borno. It was due to his considerations while being advised by the old man. The conflict of id and ego made an internal conflict for Borno. Their love story was begun from the boat. At that time, Mei was doing an internship in Pontianak. She crossed the Kapuas river by boat. Borno saw it then he fell in love with the Indo-Chinese breed girl. The red packet, angpau merah, was left on a pincher made Borno wanted to return it. Borno always kept an eye on Mei. He even remembered what time Mei went to teach and always kept trying to ensure his boat be always in the thirteenth line. It was the line in which Mei would be on board every morning.